ANALISIS VIKTIMOLOGI DAN PERLINDUNGAN HUKUM TERHADAP KORBAN PENIPUAN ONLINE DI MEDIA SOSIAL - Taufik Hidayat Batubara; Gilang Ade Prabowo (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
The rapid growth of information and communication technology has increased the use of social media, but it has also contributed to the rise of cybercrime, particularly online fraud. This study aims to analyze online fraud on social media from a victimological perspective and to examine legal protection for victims in Indonesia. The research uses a normative juridical method with statutory and conceptual approaches. The results show that victims are often vulnerable due to low digital literacy, high trust in perpetrators, and lack of information verification. Victims experience both financial and psychological harm. Legal protection remains inadequate, as it focuses more on punishing offenders than restoring victims’ rights. Although regulations exist under the Criminal Code and the Electronic Information and Transactions Law, their implementation faces challenges. Therefore, stronger regulations, improved digital literacy, and enhanced victim protection mechanisms are needed